Gamma Radiation Exposure Towards Shelf-Life Extension of Brine-Treated Indigenous Climbing Perch, Anabas testudineus (Bangladesh Journal of Zoology, 2022)
The study was conducted to evaluate the effects of gamma radiation (1.5 and 3.5 kGy) on quality and shelf-life of brine-treated (18% NaCL) cultured and indigenous Climbing perch, Anabas testudineus during storage at low temperature (4°C) through sensory (Organoleptic Score, OS), chemical (Tyrosine Value, TV) and microbial analyses (Total Bacterial Count, TBC; Total Salmonella and Shigella Count, TSS; and Total Staphylococcus Count, TSC) at weekly intervals for a period of 35 days. The quality of both cultured and indigenous perch deteriorated with the increase of time. The values of TV (23.69 – 86.20 mg/100 g) and TSS (0 – 4.43 cfu/g) were tended to be high in non-irradiated perch while the values of TBC (3.00 – 11.63 cfu/g) and TSC (2.00 – 6.52 cfu/g) showed increasing trends in irradiated samples for both stains. The findings demonstrated that the synergistic effects of brine and gamma radiation in combination with low temperature could be the most effective treatment for the shelf-life extension of perch and this technique might be applied for large scale preservation of any other local fishes of Bangladesh towards food security.Bangladesh J. Zool. 50 (1): 107-119, 2022